Hyperammonemia and systemic inflammatory response syndrome predicts presence of hepatic encephalopathy in dogs with congenital portosystemic shunts. - Mickey S Tivers; Ian Handel; Adam G Gow; Vicky J Lipscomb; Rajiv Jalan; Richard J Mellanby (PLoS ONE)
Hepatic encephalopathy (HE) is an important cause of morbidity and mortality in patients with liver disease. The pathogenesis of he is incompletely understood although ammonia and inflammatory cytokines have been implicated as key mediators. To facilitate further mechanistic understanding of the pathogenesis of HE, a large number of animal models have been developed which often involve the surgical creation of an anastomosis between the hepatic portal vein and the caudal vena cava. One of the most common congenital abnormalities in dogs is a congenital portosystemic shunt (cpss), which closely mimics these surgical experimental models of HE. Dogs with a cPSS often have clinical signs which mimic clinical signs observed in humans with HE. Our hypothesis is that the pathogenesis of HE in dogs with a cPSS is similar to humans with HE. The aim of the study was to measure a range of clinical, haematological and biochemical parameters, which have been linked to the development of HE in humans, in dogs with a cPSS and a known HE grade. One hundred and twenty dogs with a cPSS were included in the study and multiple regression analysis of clinical, haematological and biochemical variables revealed that plasma ammonia concentrations and systemic inflammatory response syndrome scores predicted the presence of HE. Our findings further support the notion that the pathogenesis of canine and human HE share many similarities and indicate that dogs with cPSS may be an informative spontaneous model of human HE. Further investigations on dogs with cPSS may allow studies on HE to be undertaken without creating surgical models of HE thereby allowing the number of large animals used in animal experimentation to be reduced.